ОРГАНИЗАЦИЯ ПОДГОТОВКИ И ПОДГОТОВКИ СТУДЕНТОВ – ФУТБОЛИСТОВ В УСЛОВИЯХ СДАЧИ ПРОГРАММЫ В ГОДИЧНОМ ЦИКЛЕ - Сейтмуратов, Т.Ш. (SCIENCE and SOCIETY, 2021)
Preparation and planning of the training process of football-students is the main direction of the educational process of the specialty of physical training. In the article, the author analyzed the training of football students by a variety of parameters and characteristics. The main assessments of the integral training of students were shown in the tables.